Pengaruh Brand Awareness dan Lifestyle terhadap Minat Beli Produk IQOS di Kota Medan (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of Brand Awareness and lifestyle on the purchase intention of IQOS products in Medan City. The background of this research is based on the shifting consumption patterns of urban society, which increasingly prioritizes health and modern lifestyles, leading to a transition from conventional cigarettes to alternative tobacco products. The research method applied is quantitative with an associative approach, using questionnaires and literature studies. The results show that Brand Awareness has a positive and significant effect on purchase intention, with recognition as the most dominant indicator. Lifestyle also significantly affects purchase intention, with opinion as the most influential indicator. Simultaneously, Brand Awareness and lifestyle have a significant impact on purchase intention, with exploratory interest as the highest indicator. These findings emphasize that strong brand identity and lifestyle compatibility are key factors in enhancing consumer interest and potential purchases of IQOS in the urban market.